(untitled) (Ius Novum, 2024)
This article is scientific and research-oriented, analysing the right, granted by the Act of 26 July 2024,1 which amends certain acts to improve the functioning of the Armed Forces of the Republic of Poland, the Police, and the Border Guard in the event of a threat to state security. The right concerns a request for the appointment of public counsel for the defence by a soldier, a police officer, or a Border Guard officer accused of a crime committed as a result of the use of direct coercive measures, weapons, or other armaments, or the application or use of coercive measures or firearms in connection with the performance of specific official activities or tasks (Article 78a of the Code of Criminal Procedure). The article also examines the broader possibilities of providing financial support to soldiers for covering the costs of legal assistance incurred in cases concerning crimes committed in connection with the performance of official tasks and activities (Article 296(5) and Article 316(5) of the Act on the Defence of the Homeland). Additionally, provisions authorising the reimbursement of legal assistance costs to officers of certain other services are analysed. The main scientific objective is to assess the justification for introducing these amendments to criminal procedure law, as well as existing solutions that privilege soldiers and officers of certain services in terms of access to counsel for the defence. The main research theses aim to demonstrate that these changes result in a violation of the principle of equality before the law. The results of the study are original, as they highlight the need for legislative intervention. The study holds significant value for both academia, as it offers a dogmatic analysis and substantial theoretical insights, and for practical application, as it suggests directions for interpretating the criteria for applying the new provisions, potentially contributing to their uniform application.